2006
DOI: 10.1111/j.1751-908x.2006.tb01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference Materials in Geoanalytical Research ‐Review for 2004 and 2005

Abstract: This review gives an overview of the use and development of reference materials of geochemical and environmental interest in the literature of the years 2004 and 2005. In these years the performance of existing methods has been improved and new geochemical applications using new techniques have been developed. Accordingly, there was an increasing need for new reference materials, especially for in situ microanalysis and for precise stable isotope measurements. In addition, there was a notable trend for further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 91 publications
1
20
0
Order By: Relevance
“…We have measured seven silicate glass standards: six MPI‐DING standards, prepared by Jochum and co‐workers,7, 8 and one NIST glass, SRM 610,9 in order to determine practical secondary ion yields and RSFs for a range of major and trace elements when using Au‐cluster SIMS. As the abundances of Li, Mg, V, Cr, Cs and Ba are not included on the original NIST certificate for SRM 610, these were instead taken from Pearce et al 10 Sputter rates for Au + , Au 2+ and Au 3+ ions have also been determined using the SRM 610 standard.…”
mentioning
confidence: 99%
“…We have measured seven silicate glass standards: six MPI‐DING standards, prepared by Jochum and co‐workers,7, 8 and one NIST glass, SRM 610,9 in order to determine practical secondary ion yields and RSFs for a range of major and trace elements when using Au‐cluster SIMS. As the abundances of Li, Mg, V, Cr, Cs and Ba are not included on the original NIST certificate for SRM 610, these were instead taken from Pearce et al 10 Sputter rates for Au + , Au 2+ and Au 3+ ions have also been determined using the SRM 610 standard.…”
mentioning
confidence: 99%
“…MC‐ICP‐MS with use of a collision cell is a powerful method to measure the isotope abundance ratios of iron as well as other elements with serious polyatomic interferences 7. We found that argon‐based interferences on masses 54, 56 and 57, mainly 40 Ar 14 N, 40 Ar 16 O and 40 Ar 16 OH, could be completely removed.…”
Section: Discussionmentioning
confidence: 92%
“…2005, Jochum et al. 2005, Jochum and Willbold 2006) were used for external calibration following the method outlined in Liu et al. (2008a).…”
Section: Methodsmentioning
confidence: 99%